Malaysia's canvas the blistering saga of a flash in the pan art revolution - Springer, James H. (Gerakbudaya Enterprise, 2019)
In February 2014, an international colony of young, freewheeling and footloose artists held a group exhibition that would stand as a pivotal turning point for the future of George Town, Penang. It was an exhibition destined to make the artists household names, infamous for boldly swinging into parties and installing challenging art onto Southeast Asian walls. It would also spell the return of George Town to a worldwide destination, a city relegated to backwater ashes rising to heights shared by heritage, culture, and cosmopolitanism. In this personal exposé, James H. Springer documents the lives and times of artists during the period of 2010 to 2016, telling the story of George Town's gentrification through their own influential experiences. Through childhood memories, artistic inspirations, fluctuating relationships and artwork - learn how these young artists lay a new path for George Town going into unpredictable times. During what could arguably be described as Malaysia's most troubling political era, Springer describes how the flourishing of art in George Town gave its population a much needed respite from federal government tomfoolery. In addition, George Town's rising art scene gave Penang State a leg up in economic prosperity, creating an unheard of level of opportunity that would either be capitalised on or squandered. Malaysia's Canvas lays bare the reality of being an artist in a developing country and the change it can inspire, with no holds barred.